2011
DOI: 10.1108/13619321111202313
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between personal debt and mental health: a systematic review

Abstract: PurposeThe purpose of this paper is to evaluate the evidence on the extent to which personal debt impacts on mental health, and mental health on personal debt.Design/methodology/approachThe paper systematically reviews the English‐language, peer‐reviewed literature, 1980‐2009, drawing on 14 databases across the medical, business, legal, and social science fields.FindingsFrom 39,333 potential papers identified, 39,283 were excluded, and 50 were reviewed using a narrative analysis approach. Among nine longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 48 publications
8
133
0
4
Order By: Relevance
“…Currently the average UK family owes more than £11k in unsecured debt (AVIVA, 2013). Similarly in the US there is currently $660 billion in outstanding credit card debt (Federal Reserve Bank of New York, 2013) DEBT AND HEALTH There has been a previous review into personal debt and mental health (Fitch, Hamilton, Bassett, & Davey, 2011). However this did not examine relationships with physical health, although the literature shows a strong relationship between physical and mental health (Scott, et al, 2009), and did not examine relationships with substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Currently the average UK family owes more than £11k in unsecured debt (AVIVA, 2013). Similarly in the US there is currently $660 billion in outstanding credit card debt (Federal Reserve Bank of New York, 2013) DEBT AND HEALTH There has been a previous review into personal debt and mental health (Fitch, Hamilton, Bassett, & Davey, 2011). However this did not examine relationships with physical health, although the literature shows a strong relationship between physical and mental health (Scott, et al, 2009), and did not examine relationships with substance use.…”
Section: Introductionmentioning
confidence: 99%
“…Equally though, access to microcredit, by nature, involves becoming indebted and there is a wide literature suggesting indebtedness contributes to the development of mental health problems (Fitch et al, 2011). Similarly, while self-employment (a potential outcome of microcredit for enterprise) has long been associated with greater autonomy and control over decision making (Eden, 1975;Lewin-Epstein and Yuchtman-Yaar, 1991;Parslow et al, 2004), studies also show self-employed individuals are considered to be more susceptible to isolation and job stress (Chay, 1993;Dellot, 2014;Jamal, 1997;Lewin-Epstein and Yuchtman-Yaar, 1991) and, for some, this could be a precarious form of employment (Benach et al, 2000;Facey and Eakin, 2010).…”
Section: Microcredit and Its Potential As A Public Health Initiativementioning
confidence: 99%
“…45 Our intervention was based on the assumption that social context plays an important role for mental illness onset and recovery, particularly in the case of debt and depression. 40 Our intervention brought together two existing services: (1) primary care mental health services provided by general practices, supplemented by Improving Access to Psychological Therapies (IAPT) services in England, and in Wales a variety of counselling and psychological therapies services; and (2) debt counselling provided by third-sector providers, such as CAB (see Figure 1). …”
Section: Intervention: Theory and Developmentmentioning
confidence: 99%
“…Fitch et al 40 conducted a systematic narrative analysis of peer-reviewed literature on the relationship between personal debt and mental health. They found that indebtedness may contribute to the development of mental health difficulties and mediate accepted relationships between those difficulties and poverty and low income.…”
Section: Introductionmentioning
confidence: 99%